2022
DOI: 10.1007/s10393-022-01590-y
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus and Paramyxovirus Shedding by Bats in a Cave and Buildings in Ethiopia

Abstract: Bats are important hosts of zoonotic viruses with pandemic potential, including filoviruses, MERS-Coronavirus (CoV), SARS-CoV -1, and likely SARS-CoV-2. Viral infection and transmission among wildlife are dependent on a combination of factors that include host ecology and immunology, life history traits, roosting habitats, biogeography, and external stressors. Between 2016 and 2018, four species of insectivorous bats from a readily accessed roadside cave and buildings in Ethiopia were sampled and tested for vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 71 publications
0
6
1
Order By: Relevance
“…pumilus remains high at elevations greater than 1500 m. This finding is somewhat contradictory to earlier studies in which M . pumilus has not been captured at elevations above 1400 m (Benda et al., 2019; Katunzi et al., 2021; Lane et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…pumilus remains high at elevations greater than 1500 m. This finding is somewhat contradictory to earlier studies in which M . pumilus has not been captured at elevations above 1400 m (Benda et al., 2019; Katunzi et al., 2021; Lane et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We then determined whether these species were present in urban (including suburban or peri‐urban) areas within their range (personal communication P. Webala, I. Tanshi and M.C. Schoeman; and Ancillotto et al, 2015; Andreani et al, 2019; Dekker et al, 2013; Fenton et al, 2002; Geldenhuys et al, 2013; Hoye & Spence, 2004; Jacobs & Barclay, 2009; Kurek et al, 2020; Lane et al, 2022; Legakis et al, 2000; O'Malley et al, 2020; Roswag et al, 2019; Schoeman, 2016; Schoeman & Waddington, 2011; Taylor et al, 1999; Wojtaszyn et al, 2013) and recorded this information as presence (1) or absence (0) in urban areas. We categorized roost specificity for each species as: utilizing 1 roost type = high, 2 roost types = medium, and ≥3 roost types = low.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies conducted in Africa showed that a large diversity of alpha and beta-CoVs was detected in different bat species [114][115][116][117][118][119][120][121]. In Kenya, detected bat CoVs were phylogenetically different from human and animal CoVs based on sequence analysis of ORFs of these viruses [122].…”
Section: Africamentioning
confidence: 99%